EFEKTIVITAS KONSELING KELOMPOK ACCEPTANCE AND COMMITMENT THERAPY DENGAN TEKNIK COGNITIVEDEFUSION UNTUK MENGATASI OVERTHINKING PADA SISWA XI B.1 SMA NEGERI COLOMADU TAHUN AJARAN 2024/2025 - Wibowo, Brigita; jawandi, Ahmad; Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
EFEKTIVITAS KONSELING KELOMPOK ACCEPTANCE AND COMMITMENT THERAPY DENGAN TEKNIK COGNITIVE DEFUSION UNTUK MENGATASI OVERTHINKING PADA SISWA XI B.1 SMA NEGERI COLOMADU TAHUN AJARAN 2024/2025. The purpose of this study is to determine the effectiveness of group counseling services using Cognitive Defusion techniques in reducing Overthinking behavior among students in class XI B.1 at Colomadu State High School in the 2024/2025 academic year. Overthinking, or excessive thinking, can be both a positive and negative issue. Acceptance and Commitment Therapy (ACT) focuses on acceptance to address all issues and encourages individuals to take meaningful actions to resolve each problem. Cognitive Defusion reduces resistance to unpleasant thoughts or experiences. This study employed an experimental design with a One-Group Pretest-Posttest approach. The research subjects consisted of 7 students from class XI B.1 selected through Purposive Sampling. The instrument used was a questionnaire measuring the level of Overthinking behavior among students before and after group counseling. The data were analyzed using a t-test, with a significance level of 0.018 < 0.05, leading to the rejection of H0 and acceptance of Ha. It can be concluded that there is a difference in the average scores before and after the treatment, indicating that group counseling using the Cognitive Defusion technique is effective in reducing Overthinking behavior among students in class XI B.1 at SMA N Colomadu for the 2024/2025 academic year. Keywords: Overthinking, Acceptance Commitment Therapy, Cognitive Defusion